2022
DOI: 10.1007/s10899-022-10113-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Mandatory Play Break on Subsequent Gambling Behavior among British Online Casino Players: A Large-Scale Real-World Study

Abstract: In recent years, various novel responsible gambling (RG) tools have been implemented to aid harm-minimization. One such RG tool has been the implementation of enforced mandatory play breaks. Despite many responsible gambling operators using mandatory play breaks, only three previous studies have examined their efficacy and the findings were mixed. Therefore, the present investigation was a large-scale real-world study which was designed to see whether a 60-minute mandatory play break influenced subsequent depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Given that one recent study showed that a 60-min mandatory break after making ten monetary deposits in one day has positive effects on gamblers' deposit and wagering behavior (Auer & Griffiths, 2022b), future studies could implement multiple triggers for mandatory play breaks (e.g., after several losses within a short period of time) and evaluate their efficacy. Evaluating different types of personalized feedback (e.g., normative feedback and potential money savings) during such mandatory play breaks is also an important avenue for the future research.…”
Section: Discussionmentioning
confidence: 99%
“…Given that one recent study showed that a 60-min mandatory break after making ten monetary deposits in one day has positive effects on gamblers' deposit and wagering behavior (Auer & Griffiths, 2022b), future studies could implement multiple triggers for mandatory play breaks (e.g., after several losses within a short period of time) and evaluate their efficacy. Evaluating different types of personalized feedback (e.g., normative feedback and potential money savings) during such mandatory play breaks is also an important avenue for the future research.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, there is a moderate short-term impact when pop-up messages are presented thus interrupting the gambling behavior ( Bjørseth et al, 2020 ). While recent evidence indicates that mandatory breaks are not an effective tool to reduce monetary stakes or the length of gambling time ( Auer and Griffiths, 2023 , Hopfgartner et al, 2022 , Hopfgartner et al, 2023 ), money and gambling time might not be the crucial drivers of gambling-related problems. Rather, excitement caused by the activity of gambling was argued to be a more relevant trigger for problematic gambling behavior than monetary gains ( Brown, 1986 ).…”
Section: Introductionmentioning
confidence: 99%
“…”). Moreover, some researchers in the gambling studies field have emphasized the importance of behavioral aspects in the identification of problem gambling – even before the rise in popularity of online gambling (e.g., Auer & Griffiths, 2023 ; Catania & Griffiths, 2022 ; Delfabbro et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%